2005
DOI: 10.1038/nature03205
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cap-dependent translation by eIF4E inhibitory proteins

Abstract: Eukaryotic messenger RNAs contain a modified guanosine, termed a cap, at their 5' ends. Translation of mRNAs requires the binding of an initiation factor, eIF4E, to the cap structure. Here, we describe a family of proteins that through a shared sequence regulate cap-dependent translation. The biological importance of this translational regulation is immense, and affects such processes as cell growth, development, oncogenic transformation and perhaps even axon pathfinding and memory consolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
827
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 877 publications
(852 citation statements)
references
References 39 publications
(37 reference statements)
11
827
0
14
Order By: Relevance
“…It should be noted that this eIF4E-binding motif contains a non-consensus charged arginine residue in the last position instead of a hydrophobic one (Figure 5b), which could result in relatively weak binding. This finding may reflect the requirement for an additional specific interaction of DDX3 with mRNA to support the effective DDX3-eIF4E interaction as is the case with several eIF4E-binding proteins (Richter and Sonenberg, 2005). Alternatively, but not exclusively, the weak interaction between eIF4E and the C-terminus of DDX3 characterized here (Figure 5a) may contribute to enhancing this interaction.…”
Section: Ddx3 Interacts With Eif4e and Regulates Translation J-w Shihmentioning
confidence: 66%
See 4 more Smart Citations
“…It should be noted that this eIF4E-binding motif contains a non-consensus charged arginine residue in the last position instead of a hydrophobic one (Figure 5b), which could result in relatively weak binding. This finding may reflect the requirement for an additional specific interaction of DDX3 with mRNA to support the effective DDX3-eIF4E interaction as is the case with several eIF4E-binding proteins (Richter and Sonenberg, 2005). Alternatively, but not exclusively, the weak interaction between eIF4E and the C-terminus of DDX3 characterized here (Figure 5a) may contribute to enhancing this interaction.…”
Section: Ddx3 Interacts With Eif4e and Regulates Translation J-w Shihmentioning
confidence: 66%
“…It has been reported that several eIF4E-binding proteins recognize eIF4E via a consensus YxxxxLF motif (reviewed by Sachs and Varani, 2000;von der Haar et al, 2004;Richter and Sonenberg, 2005). Careful inspection of the eIF4E-binding region within DDX3 identifies a potential eIF4E-binding motif (YIPPHLR) at amino-acid residues 38-44 (Figures 5b and c).…”
Section: Ddx3 Interacts With Eif4e and Regulates Translation J-w Shihmentioning
confidence: 94%
See 3 more Smart Citations